PHARMACOEPIDEMIOLOGICAL AND PHARMACOECONOMIC ANALYSIS OF TREATMENT OF ENDOMETRIT IN-HOSPITAL - L. Yu. Chernikova; M. V. Belousov (Бюллетень сибирской медицины)
Pharmacoepidemiological and pharmacoeconomical analysis of endometrit drug therapy at special treatment-and-prophylactic institutions of the city of Tomsk. Estimate the intensity of the appointment of antibacterial drugs endometrit therapy using the methodology of the WHO ATC/DDD, calculated indicators of the intensity of the consumption of drugs in the course of treatment per patient. It was shown that 70% of the established daily dose had to beta-lactam antibiotics and macrolide. For the most common options for antibiotic therapy established nosology of the indicators of clinical efficacy. The calculation of the cost of the schemes of antibiotic therapy, which showed that the cost of treatment is maximal during therapy with ceftriaxone + clarithromycin (4902 RUR); further descending follow: amoxicillin / clavulanic acid + roxithromycin (4658 RUR); benzylpenicillin and gentamicin (4231 RUR). Economic efficiency of antibacterial treatments endometritis a “cost – effectiveness”. The cost of the patient, achieved remission, made during therapy with amoxicillin/clavulanic acid and roxithromycin (5416 RUR), During therapy with ceftriaxone and clarithromycin (6052 RUR), the treatment of benzylpenicillin and gentamicin (14420 RUR). Pharmacoeconomic evaluation results showed that the least acceptable scheme of antibacterial therapy of endometrit in the hospital is the combination of benzyl penicillin and gentamicin. Тhe antibiotic therapy for endometrit may be recommended by a combination of amoxicillin / clavulanic acid and roxithromycin and clarithromycin and ceftriaxone, for which there was no statistically significant differences in clinical efficacy and cost of antibiotic therapy.